2020
DOI: 10.3390/toxins12050287
|View full text |Cite
|
Sign up to set email alerts
|

MazF Endoribonucleolytic Toxin Conserved in Nitrospira Specifically Cleaves the AACU, AACG, and AAUU Motifs

Abstract: MazF is an endoribonucleolytic toxin that cleaves intracellular RNAs in sequence-specific manners. It is liberated in bacterial cells in response to environmental changes and is suggested to contribute to bacterial survival by inducing translational regulation. Thus, determining the cleavage specificity provides insights into the physiological functions of MazF orthologues. Nitrospira, detected in a wide range of environments, is thought to have evolved the ability to cope with their surroundings. To investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…The amino acid sequences of MazFs from several species, the cleavage sequences (ACA, UAC, AACU, UACA, and UACAU) of which are similar to the UACAAA recognition sequence of MazF-Da ( Zhang et al, 2003b ; Zhu et al, 2009 ; Park et al, 2011 ; Rothenbacher et al, 2012 ; Yamaguchi et al, 2012 ; Schuster et al, 2013 ; Miyamoto et al, 2016a , b , 2017 , 2018 ; Shaku et al, 2018 ; Ishida et al, 2019 ; Aoi et al, 2020 ), were selected for multiple alignment. We identified Gly6 (G6), Pro15 (P15), Gly18 (G18), Glu20 (E20), Arg25 (R25), Pro26 (P26), Asn36 (N36), and Arg85 (R85) as highly conserved sites ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid sequences of MazFs from several species, the cleavage sequences (ACA, UAC, AACU, UACA, and UACAU) of which are similar to the UACAAA recognition sequence of MazF-Da ( Zhang et al, 2003b ; Zhu et al, 2009 ; Park et al, 2011 ; Rothenbacher et al, 2012 ; Yamaguchi et al, 2012 ; Schuster et al, 2013 ; Miyamoto et al, 2016a , b , 2017 , 2018 ; Shaku et al, 2018 ; Ishida et al, 2019 ; Aoi et al, 2020 ), were selected for multiple alignment. We identified Gly6 (G6), Pro15 (P15), Gly18 (G18), Glu20 (E20), Arg25 (R25), Pro26 (P26), Asn36 (N36), and Arg85 (R85) as highly conserved sites ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Haloquadratum walsbyi, isolated from a hypersaline pool in the Sinai Peninsula, possesses a unique MazF that recognizes the longest known recognition sequence, consisting of seven bases (UUACUCA) ( Yamaguchi et al, 2012 ). More recently, the MazF homologs of Methanohalobium evestigatum and the Nitrospira strain ND1 have been shown to recognize not just one but multiple sequences ( Ishida et al, 2019 ; Aoi et al, 2020 ). These studies show that MazF toxins, which are conserved in various species, are unique ribonucleases with different recognition sequences and lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the above homology, the cross-neutralization between MazF and non-cognate MazE was examined, revealing the obvious suppression of MazE-bs on MazF-sth. The structure mechanism was analyzed by multiple sequence alignment (MSA) [ 11 , 13 , 14 , 16 , 17 , 18 , 19 , 20 , 25 , 26 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] ( Figure S5 ) combined with the simulation of the MazEF-sth complex structure via AlphaFold2 [ 48 ] ( Figure S6 ). Focus was placed on the interface; next, regions of the MazF-sth dimer interacting with MazE-sth were estimated as follows and highlighted with red/blue squares on MSA ( Figures S5 and S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Aoi et al reported that, in Nitrospira strain ND1, the MazF toxin specifically recognizes the motifs AACU, AACG, and AAUU [ 15 ]. However, since, in this case, MazF target is not a coding triplet, a bias in the reading of the genetic code should not be characteristic for genes that specify stress-induced MazF mediated proteins of Nitrospira strain ND.…”
Section: Introductionmentioning
confidence: 99%